P229 Feasibility of cardiopulmonary exercise testing in idiopathic pulmonary fibrosis. (December 2018) - Wollerton, RL; Tomlinson, OW; Knight, BA; Duckworth, A; Spiers, A; Williams, CA; Gibbons, M; Scotton, CJ
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive interstitial lung disease of irreversible declining lung function. Reductions in forced vital capacity (FVC) and diffusion capacity for carbon monoxide (DLCO ) are the common clinical endpoints for prognostic monitoring and assessing treatment outcomes. The use of cardiopulmonary exercise testing (CPET) in IPF remains largely unexplored. Objectives: To explore the feasibility of CPET as a clinical measure in IPF and identify associations with established clinical variables. Methods: Seventeen patients with IPF were approached, and fifteen (88%) were recruited (13 male, 68.1±7.5 years). Incremental exercise testing to exhaustion was undertaken via electronically braked cycle ergometer. Variables included: peak oxygen consumption (VO2peak ), peak work rate (WRpeak ), nadir SpO2, ventilatory drive (VE /VCO2 ), alongside standard clinical pulmonary function tests of FVC and DLCO . Pearson's correlation coefficients established relationships between variables. Results: One participant was excluded (high baseline systolic blood pressure). Eight out of fourteen (57%) participants reached volitional exhaustion. Five CPETs were terminated early due to desaturation (SpO2 <88%) and one to an exercise-induced right bundle branch block (recovery within minutes of ceasing exercise). Mean (±SD) pulmonary and exercise results were: FVC, 84.9%±17.0%; DLCO, 56.5%±11.4%; VO2peak, 1.4±0.4 L.min -1, 16.5±5.5 mL.kg -1 .min -1 ; WRpeak, 104±42 W; SpO2, 90±3%; VE /VCO2, 27.1±6.4. Significant correlations were identified between: FVC and SpO2 ( r =0.58, p=0.032), DLCO and VE /VCO2 ( r =0.81, p<0.001) and WRpeak ( r =0.58, p=0.03). Body-mass relative VO2peak held moderate, but not significant relationships with FVC ( r =0.44, p=0.11) and DLCO ( r =0.53, p=0.51). Conclusions: Initial findings from this study have found CPET to be acceptable to patients with IPF and potentially feasible as a testing measure. Preliminary results identified common exercise desaturation, suggesting less conservative SpO2 termination criteria (e.g. 80% cut-off) could be considered. Although exercise parameters held limited relationships with FVC and DLCO, results from VO2peak identifies potential additional and dynamic prognostic information and warrants further investigation.